Is the Tour Guide’s Competency Important to Increase Tourist Satisfaction? - Trivenna, Lady; Eviana, Nova (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
As frontline workers who interact with tourists, tour guides play an essential role in improving the travel experience and creating tourist satisfaction. Consequently, tour guides must possess professional competence to perform their duties effectively. This research aims to analyze the influence of tour guides' competence on tourist satisfaction at the Jakarta History Museum, a prominent tourist attraction and historical tourism asset in Jakarta. The study employed a survey method involving 100 tourists of the Jakarta History Museum who had utilized the services of tour guides as respondents. The data analysis was conducted using multiple linear regressions. The results indicated that the competence of tour guides had a positive and significant impact on tourist satisfaction. Although knowledge alone did not significantly contribute to tourist satisfaction, the professional skills and attitudes of the tour guides had a notable positive effect. The competence of tour guides accounted for 47.748% of the variation in tourist satisfaction. Therefore, enhancing the competence of tour guides is essential to ensuring tourist satisfaction.